Improving results management processes in an acute hospital using a multi-faceted approach. (28th December 2021) - Koh, Darrel; Wee, Tracy; Fong, Michelle; Tan, Xiaohui; Tan, Rudyanna; Menon, Shalini; Goh, Joey; Teo, Stephanie; Chia, Joanna; Kristanto, William; Lim, Ghee Hian
Abstract: Background: Radiological examinations and laboratory tests are routinely ordered by hospital physicians as part of the care plan to diagnose and treat patients. However, the failure to actively review and follow-up on these results pose a significant problem to patient safety. A study team was formed to mitigate the clinical risks of poor results management, which was identified as a top clinical risk in our organization, in order to make improvements to the results management process and to ensure the timely review, acknowledgement and follow-up of test results. Objective: This study was carried out to improve results management processes and ensure the timely review, acknowledgment, and follow-up of test results, in order to mitigate the clinical risks posed to patient safety. Methods: The institutional expectations of results management were set and published as a hospital policy, which was communicated to all clinical departments for compliance. Improvements to the electronic medical records system were made to facilitate the results acknowledgement process, and physicians were engaged to educate them on the importance of results management. Results: The study team observed a decrease in unacknowledged results from approximately 16 000 in March 2017 to 2673 in December 2020. The compliance rate for acknowledgement results increased from a monthly average of 83.7% (from March to December 2017) to a monthly average of 99.3% (in 2020). The risk score for results management decreased from 16 to 6.5 and was excluded from the organization's top clinical risks. Conclusion: This study showed the importance of both system improvements and culture changes that are required to improve the process of results management and provides a step forward for the hospital to safeguard patient safety and mitigate clinical risk.